Relationships between death anxiety and quality of life in Iranian patients with cancer - Mohammad A Soleimani; Rebecca H Lehto; Reza Negarandeh; Nasim Bahrami; Hamid Sharif Nia (Elsevier, 2016)
Objective: The purpose of the study was to examine relationships between death anxiety and quality of life (QOL) parameters of patients with cancer in the Iranian sociocultural context. Methods: A descriptive, correlational methodology was used. The sample included 330 patients. Demographics, health information, religious behaviors, death anxiety, and QOL data were collected. Results: Overall death anxiety levels were moderate with satisfactory overall QOL. Death anxiety was predictive of lowered QOL. Female patients had lower QOL and higher death anxiety compared to men Conclusions: Findings support that higher death anxiety negatively impacts QOL in an Iranian sample with cancer. Alleviation of existential concerns in vulnerable patients may palliate mental health distress associated with facing cancer and its challenging treatments.